Implementing Problem-Based Learning to Improve Collaborative Writing Skills through Lesson Study in the Indonesian Language Subject - Fawaid, Achmad; Huda, Miftahul (Universitas Muhammadiyah Malang, 2024)
The time constraints, lack of resources, and conventional teaching methods often make students lose interest in writing skills. This article analyses the implementation of problem-based learning approaches through lesson study as an effective solution to enhance students’ writing skills collaboratively on Indonesian language subject. The lesson study activity directed in applying problem-based learning was done as much as six times with writing skills material. The research was conducted with a participatory based qualitative approach to six different classes at SMAN 2 Tanggul Jember, each consisting of an average of 35 students. Data related to writing skills were collected through student work sheets, while data related to collaboration were collected through observation sheets. This study resulted in an increase in the aspect of writing skills performed by the model teacher and lecturer in six open classes. More students scored between 61-80, meeting the criteria of BSH (Developing as Expected). On the other hand, improvements have also been observed in the process of inter-student collaboration in writing. For example, a few students who were previously idle in the classroom became more engaged, the teaching process began to be structured, and student activity within groups increased. In conclusion, problem-based learning, practiced through study lessons, has significantly enhanced students’ collaborative writing skills at the Senior High School level.